Is God in Nigeria? Land dislocation and the challenge of confessing Belhar in Nigeria today - Akper, Godwin (Stellenbosch Theological Journal, 2018)
Of the view that "in the land full of enmity, God is in a special way the God of the destitute and the wronged", the essay explores the challenge of confessing the third article in the Confession of Belhar in Nigeria today. Nigeria has recorded a high number of displaced persons in the years between 1982 and 2016, who have been dispossessed of their lands and their hopes for better living standards. This situation has often been caused by the activities of radical religious activists. Also, a number of communal crises among ethnic nationalities especially in some parts of what can be described as northern Nigeria have added to the statistics of Internally Displaced Persons (IDPs). These destitute, many of whom are Christians, continuously cry out, hoping that God may intervene, and change their situations for the better, but seemingly to no avail. For some of them, it seems like all hope is lost. With such agonising situations among Christians, what sense will it make, "to preach" to them that "œGod is in a special way" their God? The essay examines this question by juxtaposing the Nigerian situation with South Africa's past, when the Christians in South Africa confessed that God was still on their side amidst a seemingly hopeless situation. It also explores whether some lessons from the South African experience can be of any assistance or relevance to the Christians in Nigeria today.